Synaptic mechanisms underlying the elevated sympathetic outflow in fructose-induced hypertension - Zhu, Yun; Sun, Haiying; Wang, Hongjie; Li, Na (Frontiers in Physiology, 2024)
The metabolic syndrome is associated with cardiovascular dysfunction including elevated sympathetic outflow. However, the underlying brain mechanisms are unclear. The nucleus tractus solitarius (NTS) critically regulates autonomic reflexes related to cardiovascular function and contains neurons projecting to the caudal ventrolateral medulla (CVLM). Nitric oxide (NO) is a diffusible free radical messenger in the vascular, immune, and nervous systems. In this study, we determine if NO in the NTS is involved in synaptic plasticity underlying elevated sympathetic outflow in fructose-induced hypertension. We retrogradely labeled CVLM projecting NTS neurons by injection of Fluospheres into the CVLM in a fructose-fed rat model to determine the cellular mechanism involved in increased sympathetic outflow. Fructose feeding increased blood pressure and glucose levels, which represent metabolic syndrome. We found that fructose feeding reduces NO precursor L-arginine-induced increase in firing activity of CVLM projecting NTS neurons. Furthermore, fructose feeding reduces Larginine-induced increase in presynaptic spontaneous glutamatergic synaptic inputs to NTS neurons, while NO donor DEA/NO produces similar increase in glutamatergic synaptic inputs in fructose-fed rats to vehicle-treated rats. In addition, fructose feeding reduces NO-induced depressor and sympathoinhibition. These data suggested that fructose feeding reduced NO production, thus, the subsequent NO-induced glutamate releases in the NTS and depressor response. Findings from this study provides new insights into central mechanisms involved in neural control of cardiovascular and autonomic functions in the NTS in metabolic syndrome.It has been shown that metabolic syndrome is associated with cardiovascular dysfunction such as heightened sympathetic outflow. The brain mechanism remains to be determined. Using a fructoseinduced metabolic syndrome rat model, this study found that fructose feeding reduces the excitatory effect of L-arginine, the precursor of a gaseous neurotransmitter nitric oxide, on the firing activity of NTS neurons. Furthermore, fructose feeding reduces L-arginine-induced increase in glutamatergic synaptic inputs to NTS neurons, but did not change the effect of NO donor DEA/NO on glutamatergic synaptic inputs. This novel finding provides new insights into central mechanisms involved in neural control of cardiovascular and autonomic functions in the NTS in metabolic syndrome.